Speaking peace : women's voices from Kashmir - Butalia, Urvashi (New Delhi : Kali for Women, 2002)
Contributed articles and interviews with women from Kashmir, India on their socio-political status.
Keywords: Women -- India -- Jammu and Kashmir -- Social conditions